The Crisis of Germany's Pension Insurance system and How it Can be Resolved - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 1999)
The paper discusses the options for a reform of the German pension system using a model developed at CES for the German Council of economic advisors to the Federal Ministry of Economics and Research. It is argued that the German pay-as-you-go-system is efficient in a present value sense but will nevertheless need the support of a funded system to avoid a financial crisis. The paper recommends obligatory priv ate savings at a variable rate where the time path of the savings rate is chosen so as to stabilize the sum of this rate and the pay-as-you-go contribution rate, given the time path of pensions as defined in the present system.
Keywords: 330; Pension insurance; pay-as-you-go system; savings; Germany